Spectral Studies of Cu(II) Complex of Substituted Schiff Based - Mehta, B.H.; Yogita Desai, Ms. (Asian Journal of Chemistry, 2010)
Schiff base ligands (L) were synthesized using 2-hydroxy-1-napthaldehydeand various primary amines like anthranilic acid,o-toluidene, p-toluidene and aniline. Copper complexes of the Schiffbase were synthesized having metal : ligand stoichiometry 1 : 1 or1 : 2. The ligands and respective copper complexes were diagnosedfor their analytical parameters and various spectral features. Thestructures of copper complexes were proposed on the basis ofelectronic absorption, IR spectra and ESR spectral data..